Data and Information Security Management: Preparing Data in the Cyber Era in Indonesia - Rosyada Amiirul Hajj; Abdul Muta'ali; Benny Jozua Mamoto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the findings that has the greatest influence in the information society is the discovery of the internet. The Indonesian government has issued a policy related to the information security management system through Minister of Communication and Information Regulation No. 4 of 2016 which regulates the Information Security Management System. One of the negative impacts that arise in cyber-space is the occurrence of cyber crime. The rise of cyber crime requires attention and seriousness in developing cyber-security for a country including Indonesia. The theory used is using the theory of cyber crime and also physical management theory. The methodology of this research uses qualitative methods. So the results of the research are recommendations made from several written sources. So that it can be a reference for future research.